Soil Organic Carbon Distribution in a Humid Tropical Plain of Cameroon: Interrelationships with Soil Properties - Georges Kogge Kome; Roger Kogge Enang; Bernard Palmer Kfuban Yerima (Applied and Environmental Soil Science)
Soil organic carbon (SOC) determination is very important in the assessment of agronomic potential of a soil. The objective of this study was to determine SOC contents and stock distribution with depth in relation to selected soil properties. Five types of soils, namely, Mollic Endoaquents, Oxyaquic Paleudalfs, Oxyaquic Udifluvents, and Mollic Udifluvents from a humid tropical plain and Typic Eutrudepts from an adjacent foot slope, were studied. The soils have all developed from fluvial sediments. Morphological and physicochemical characteristics of the soils were obtained using standard methods. Soil texture varied across the different sites and within soil profiles with textural classes of genetic horizons ranging from sandy loam to heavy clay. The soils are generally young soils under development as indicated by their high silt/clay ratios which ranged between 0.23 and 2.45. All the soils were generally acidic with pH-H2O values ranging from 4.5 to 6.2. Exchangeable H+ and Al3+ ranged from 0.5 to 2.3 and 0.2 to 3.3 cmolckg−1, respectively. SOC contents are generally higher in surface horizons and decrease with depth. In general, SOC correlated significantly with bulk density (BD) (r = −0.648, p<0.01), water holding capacity (r = 0.589, p<0.01), exchangeable Al3+ (r = 0.707, p<0.01), and exchangeable H+ (r = 0.456, p<0.05). The correlation between SOC and exchangeable Al3+ was strongest in the Mollic Endoaquents (r = 0.931, p<0.01). SOC contents correlated significantly with Munsell soil color attributes, explaining between 40 and 57% of SOC variation. Total SOC stocks at a depth of 100 cm varied between 260.1 and 363.5 t·ha−1, and the variation in SOC stocks across a profile appears to be controlled by genetic horizon depth, while land use type influences SOC stock variations across genetic surface horizons.